INTERDISCIPLINARITY AS A METHODOLOGICAL BASIS FOR ANALYSIS OF CONFLICT PHENOMENON AND THE EDUCATIONAL PROGRAMME "CONFLICTOLOGY" - Andrei V. Aleinikov; Alexandr I. Strebkov (National Research Mordova State University, 2017)
Introduction: the article deals with development patterns and the process of institutionalisation of conflictology as an educational discipline. The special attention is paid to main features of the interdisciplinary analysis of the conflict. Difficulties and problems of political and legal space of conflictology education are given a thorough account. Materials and Methods: the interdisciplinary paradigm of conflict analysis is a methodological basis of the research, which implies its consideration not only as a source of destructions and dying but as a starting place of the society development. Saint-Petersburg State University's practical experience in the implementation of the educational programme on conflictology was analysed. Results: the approval of the conflictology as a special area of knowledge is connected with theoretical understanding and practical application of the tools transforming the destructive power of conflict. Understanding of the conflict as a contradiction between struggle and peace is important heuristical instrument. Main characteristics and classification of hierarchically structured levels of functioning of the conflict theory and the educational program on conflictology are determined; the interdisciplinary nature of the curriculum and professional competences of the graduates are presented. Discussion and Conclusions: the problems, which restrain future development of conflictology as the institutionalised self-reflection of society about contradictions in Russia, are determined on the basis of the analysis of educated graduates' adaptation practices. Main directions of integration of conflictological educational programmes for training specialists of high qualification in the field of conflict resolution and peace maintenance in organisational and management sphere are presented. This is achieved by organisation of peaceful social interactions and minimisation of the conflict potential of decisions in management. The research allows to state that the main content of conflictology is determined by the necessity to reach knowledge about the system and processes of conflict and peaceful interaction, institutions, means and humanitarian technologies of conflict resolution and peace maintenance. The authors believe that the programme should be implemented on the interdisciplinary ground, systematising knowledge about conflicts and developing templates of optimal behaviour in conflict or partnership situations.